Indonesian National Social Security Management Law Problematics with the Enabling of Law Number 40 of 2004 Concerning a National Social Security System - Nurrochmah Ihayani I; Nurul Istiqomah S H; Sitti Nursanti; Budi Pramono (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study discusses legal problems that occur in the management of Indonesia’s national social securitywith the enactment of Law number 40 of 2004. This research is a normative legal research with a conceptualand statutory approach. This study uses the theory of Laurence M. Friedman as a knife of analysis that theproblem of managing national social security includes institutional structures, substance, the Healthcareand Social Security Agency and The National Social Security regulation and legal culture. It is hoped thatthe management of national social security will accelerate the transfer of management of the Savings Fundand Civil Servant Insurance Company and the Social Insurance of the Armed Forces of the Republic ofIndonesia Company, so that they do not have to wait up to 25 years.